0.25 μm emitter InP/InAlGaAs/GaAsSb double heterojunction bipolar transistor with passivation ledge exhibiting a current gain of over 100. Issue 22 (1st October 2014) - Kashio, N.; Kurishima, K.; Ida, M.; Matsuzaki, H.
Abstract : A suitable emitter structure for the fabrication of InP/InAlGaAs/GaAsSb double heterojunction bipolar transistors (DHBTs) with a passivation ledge is reported. With a composite emitter structure consisting of an InP and thin InAlGaAs, a passivation ledge can be easily fabricated by wet etching. A high current gain of 117 is obtained even for a 0.25 μm emitter DHBT with a base sheet resistance of about 1100 Ω/sq. The fabricated HBT also exhibits an f max of more than 330 GHz while maintaining a breakdown voltage of more than 9 V.